2019
DOI: 10.1136/ijgc-2018-000028
|View full text |Cite
|
Sign up to set email alerts
|

Is there uniformity in definitions and treatment of gestational trophoblastic disease in Europe?

Abstract: ObjectivesBecause gestational trophoblastic disease is rare, little evidence is available from randomized controlled trials on optimal treatment and follow-up. Treatment protocols vary within Europe, and even between different centers within countries. One of the goals of the European Organization for Treatment of Trophoblastic Diseases (EOTTD) is to harmonize treatment in Europe. To provide a basis for international standardization of definitions, treatment and follow-up protocols in gestational trophoblastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…Metastases detected on CXR, were found to be associated with an extended TNhCG, supporting the literature in low-risk patients, suggesting that pulmonary metastases present at the start of treatment are associated with higher rates of TR 7,13,15,18 and disease recurrence. 16,18 Metastases detected on CT were not associated with a longer TNhCG.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Metastases detected on CXR, were found to be associated with an extended TNhCG, supporting the literature in low-risk patients, suggesting that pulmonary metastases present at the start of treatment are associated with higher rates of TR 7,13,15,18 and disease recurrence. 16,18 Metastases detected on CT were not associated with a longer TNhCG.…”
Section: Discussionsupporting
confidence: 78%
“…Unfortunately, previously published literature comparing CXR and CT did not study these outcome measures. 7,9,13 Frijstein et al 18 demonstrated higher rates of disease recurrence amongst low-risk patients with pulmonary metastases, compared to those without pulmonary metastases. However, as our study included both low-and high-risk patients, the two studies cannot be compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FIGO 2000 risk-scoring system, including eight clinical variables, is the accepted model for stratification of women with GTN into low vs high risk of resistance to first-line single agent chemotherapy, and thereby for treatment selection 1,2 . In Europe, MTX is used widely as first-line treatment for low risk GTN 16 . Although useful, the risk-scoring system will stratify incorrectly more than one-third of all patients who will become resistant to single-agent MTX 17 , and studies have aimed at improving risk prediction in women with GTN 7,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, GTD has an incidence of 1.67 per 1,000 deliveries [3]. Given the rarity of GTD, high-level evidence is limited, and treatment protocols vary between and within countries [5]. Healthcare professionals are often unfamiliar with the management of GTD, especially in countries with limited access to specialized care.…”
Section: Introductionmentioning
confidence: 99%